The Influence of Online Customer Reviews, E-promotion, and Perceived Ease of Use on Purchase Intention - Afrenea Miranda Putri; Defrizal Defrizal (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of online customer reviews, E-promotion, and perceived ease of use on the purchase intention of cosmetic products on the Shopee Live platform. Research Methodology: This study uses a quantitative approach to test the relationship between variables and confirm hypotheses that have been formulated based on previous theories and findings. The study population was composed of all potential buyers of cosmetics during live shopping on Shopee, the exact number of which is still unknown. The sampling technique was carried out using a non-probability sampling technique, more precisely purposive sampling. The sample size was calculated using the Slovin formula so that the final number of respondents was 100. Results: The results of the study stated that online customer reviews, E-promotion, and perceived ease of use have a significant impact on purchase intention, both partially and simultaneously. Conclusions: This study concludes that businesses should manage customer reviews well, design effective promotions, and ensure ease of navigation and transactions to increase consumer buying intent. Limitations: Although the observations show a relationship between online customer reviews, E-promotion, and perceived ease of use on purchase intention, this study has limitations because it only focuses on correlational relationships and does not directly examine causality relationships or other factors that may influence customer purchase intention. Contributions: The present study contributes to cosmetic businesses by optimizing digital strategies through the live shopping feature to increase consumer interaction and purchase intention.